Vaginal Lactobacillus: biofilm formation in vivo – clinical implications - Ventolini G (Dove Medical Press, 2015)
Gary Ventolini School of Medicine, Texas Tech University Health Sciences Center – Permian Basin, Odessa, TX, USA Abstract: Vaginal lactobacilli provide protection against intrusive pathogenic bacteria. Some Lactobacillus spp. produce in vitro a thick, protective biofilm. We report in vivo formation of biofilm by vaginal Lactobacillus jensenii. The biofilm formation was captured in fresh wet-mount microscopic samples from asymptomatic patients after treatment for recurrent bacterial vaginitis. In vivo documentation of biofilm formation is in our opinion noteworthy, and has significant clinical implications, among which are the possibility to isolate, grow, and therapeutically utilize lactobacilli to prevent recurrent vaginal infections and preterm labor associated with vaginal microbial pathogens. Keywords: vaginal Lactobacillus, biofilm, vaginal flora, vaginal, bacterial, protection